BUILDING REPLACEMENT COST FOR SEISMIC RISK ASSESSMENT IN PALBAPANG VILLAGE, BANTUL SUB-DISTRICT, YOGYAKARTA INDONESIA - , Bayu Aswandono, Prof. Dr. rer. nat. Junun Sartohadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Yogyakarta region especially Bantul listed in Indonesian seismic zoning as one of the most earthquake prone city in the country. The 2006 earthquake in Bantul created a lot of victims caused by the fallen building materials. The replacement cost on building damaged by Government was not representing the appropriate way on building losses due to earthquake. For that reason, more studies on building loss estimation are needed. This research was intended to analyze the use of HAZUS methodology in building replacement cost for seismic risk assessment in Indonesian practice. HAZUS is a Geographic Information System (GIS) based software tool developed in the United States that supports the evaluation of hazards and assessment of inventory and loss estimates for the kind of hazards, in this case was earthquake hazard. The research was divided into three major stages